2015
DOI: 10.1155/2015/735868
|View full text |Cite
|
Sign up to set email alerts
|

Primary Hyperparathyroidism and Hyperthyroidism in a Patient with Myotonic Dystrophy: A Case Report and Review of the Literature

Abstract: Various endocrine manifestations are commonly described in myotonic dystrophy (MD), including primary hypogonadism, diabetes mellitus, and thyroid and parathyroid dysfunction. We describe a 46-year-old woman with a family history of MD with her son. She was diagnosed with cardiac arrhythmia and required the implantation of a pacemaker. She was noted to have a bilateral cataract. She complained of muscle weakness, diffuse myalgia, and palpitation. The electromyography (EMG) showed myotonic discharges. Laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
4
0
1
Order By: Relevance
“…5 Hypercalcaemia secondary to the primary hyperparathyroidism (PHPT) has been anecdotally reported, [6][7][8] with a recent literature review noting 34 reports of isolated PHPT due mainly to parathyroid adenomas. 9 The authors of this review suggested that PHPT may be more prevalent in patients with DM1 than previously recognised. In addition, it is noted that very few studies describe the nature of dysregulated calcium metabolism in such cases and its effects on bone health.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…5 Hypercalcaemia secondary to the primary hyperparathyroidism (PHPT) has been anecdotally reported, [6][7][8] with a recent literature review noting 34 reports of isolated PHPT due mainly to parathyroid adenomas. 9 The authors of this review suggested that PHPT may be more prevalent in patients with DM1 than previously recognised. In addition, it is noted that very few studies describe the nature of dysregulated calcium metabolism in such cases and its effects on bone health.…”
Section: Introductionmentioning
confidence: 84%
“…Endocrine and metabolic disorders in DM1 include the metabolic syndrome, impaired glucose handling, dyslipidaemia, primary hypogonadism and adrenocortical secretory insufficiency . Hypercalcaemia secondary to the primary hyperparathyroidism (PHPT) has been anecdotally reported, with a recent literature review noting 34 reports of isolated PHPT due mainly to parathyroid adenomas . The authors of this review suggested that PHPT may be more prevalent in patients with DM1 than previously recognised.…”
Section: Introductionmentioning
confidence: 97%
“…Пациентка страдала двусторонней катарактой. Лабораторные исследования выявили высокие уровни кальция, фосфора и паратгормона в сыворотке, сниженную концентрацию ТТГ и отсутствие АТ к тиреопероксидазе [14].…”
Section: Discussionunclassified
“…20,[30][31][32][33][34][35] ESR and CRP levels were found to be markedly elevated in this patient and were monitored during follow-ups (Table 1). Other laboratory tests that are supportive of suspected PMR and the exclusion of other disorders include assessment of the thyroid-stimulating hormone, 36 electrolytes, alkaline phosphatase levels, creatinine, and creatine phosphokinases. [37][38][39][40][41][42] All of these were normal in this patient (Table 1).…”
Section: Laboratory Investigationsmentioning
confidence: 99%